ANALISIS KEBANGKRUTAN SILICON VALLEY BANK TERHADAP HARGA SAHAM PT. BANK CENTRAL ASIA Tbk - Jati, Lintang Permata; Manda, Gusganda Suria (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2024)
This article explores the resilience of the banking sector in the face of rising interest rates and the global economic slowdown caused by the recent measures of the Federal Reserve System (The Fed). Based on quantitative data with descriptive analysis and data visualization, the results show that the banking sector remains strong despite the volatile stock market. Notably, Bank Central Asia (BBCA) shares show higher stability and lower risk than Silicon Valley Bank (SIVBQ) shares, which experienced significant fluctuations due to bankruptcy in March 2023. Investors tend to be more attracted to BBCA because of its stability. This study also emphasizes the importance of a thorough understanding of the internal and external factors that affect stock value, as well as the importance of prudence in investment selection to reduce the risk of loss. Future researchers are advised to expand the scope of the study by including data from more institutions and exploring other factors that affect stock performance.